Formality or Reality: Student Teachers’ Experiences of Ethical Dilemmas and Emotions During the Practicum - Wang, Xin; Liu, Denghui; Liu, Jingyan (Frontiers in Psychology, 2022)
The main purpose of the study was to explore Chinese teacher students’ experience during their practicum and what they reported as ethical dilemmas and how these experiences affected them in terms of professional development as well as emotional well-being. Through the analysis of qualitative data collected from forty-three participants’ interviews, this study identified six most commonly reported ethical dilemmas and found that dilemmas about formal curriculum versus informal and hidden curriculum were the dominant workplace ethical dilemma for teacher students. The results also showed that the majority of the student teachers reported experiencing negative emotions or painful memories, which may have a negative impact on their professional competencies and overall wellbeing. Thus, the study argues that teacher students’ frequent encounters with ethical dilemmas highlight the challenges faced by teacher educators in transferring knowledge between university and school environments, and teacher students should be equipped with essential emotional regulation strategies that could benefit them in their future work.